Presentation and Outcomes of Otolaryngologic Surgeries in Patients With Mental Illness History. (June 2023) - Al-Qurayshi, Zaid; Rossi-Meyer, Monica; Shama, Mohamed A.; Williams, Amy M.; Bayon, Rodrigo; Kandil, Emad
Background: Describe the epidemiology and characteristics of patients with a history of mental illness undergoing otolaryngologic procedures. Methods: A retrospective cross-sectional analysis utilizing the Nationwide Readmissions Database, 2010 to 2015. The study sample included adult (≥18 years) patients undergoing otolaryngologic procedures. Results: A total of 146 182 patients were included, 18.3% with mental illness history. The prevalence of patients who required otolaryngologic surgeries with history of mental illness increased significantly from 14.9% in 2010 to 25.0% in 2015 ( P < .001). Mental illness diagnoses included: depression (6.9%), anxiety (5.8%), alcohol dependence (4.2%), substance dependence (2.9%), bipolar disorder (1.4%), memory disorders (1.2%), delusional disorders (0.6%), self-harm (0.1%). Patients with a history of mental illness were more likely to be <65 years, female, and have multiple comorbidities ( P < .05 each). Patients with history of mental illness had a higher risk of complications [OR:1.59, 95% CI:1.50, 1.69, P < .001]. Conclusions: Patients with a history of mental illness are increasingly encountered in otolaryngology service. This study provides an epidemiological perspective that warrants increasing clinical investigation of this subpopulation.